A Comparison of the Antithrombotic and Haemorrhagic Effects of a Low Molecular Weight Heparin (LHN-1) and Conventional Heparin - Diness, V; Nielsen, J I; Pedersen, P C; Wolffbrandt, K H; Østergaard, P B (Thrombosis and Haemostasis, 1986)
The antithrombotic effects after intravenous administration of a low molecular weight heparin (LHN-1) and conventional heparin were compared in a rabbit model of experimental thrombosis, where thrombus formation was induced by a combination of endothelial damage and stasis. Both compounds were able to prevent thrombosis completely. However, LHN-1 was significantly less potent than conventional heparin, the ratio between doses with the same antithrombotic effect being 2.4:1 on a weight basis. Bleeding times after administration of LHN-1 and conventional heparin were determined by tail transsection in anaesthetized rats and by template bleeding in the ear of conscious pigs. Given intravenously at a dose ratio of 2.4:1 (w/w), LHN-1 affected APTT less than conventional heparin, whereas the effects on haemostasis were not significantly different. In conclusion, it was found that after intravenous administration LHN-1 prevented experimental thrombosis as effectively as conventional heparin. However, the correlation between antithrombotic and haemorrhagic effects of LHN-1 was the same as that of conventional heparin. The corresponding relation in man remains to be determined.
Keywords: LMW heparin; Venous thrombosis; Bleeding; Experimental Summary